Accompagner les pratiques masturbatoires des adolescent.e.s dans des institutions pour personnes dites autistes : gestion du collectif, crainte de l’intime - Adrien Primerano (Genre, Sexualité et Société)
Drawing on a fourteen-month ethnographic study conducted within three specialized institutions for young people designated as autistic, and thirty interviews with its professionals, this article addresses discourses and practices related to masturbation. While sexuality is officially prohibited within these institutions, masturbation is legitimized in the name of exploring the body and as a symbol of adolescence. However, the way of addressing masturbation varies according to gender: for boys, there’s more openness and discussion. A concerted and collective behaviour management can provide support for making masturbatory acts private. Nonetheless, even though masturbation might be seen as a practice requiring learning in order to achieve pleasure or to avoid frustration, there is no consensus among professionals on how to get these skills or if it is necessary.